Saphenous Vein Graft Aneurysms: A Growing Problem? Presentation of Two Cases and Surgical Management - Zientara, Alicja; Dzemali, Omer; Odavic, Dragan; Genoni, Michele (The Thoracic and Cardiovascular Surgeon Reports, 2014)
Background Saphenous vein graft aneurysm is a rare complication after coronary artery bypass grafting leading to reoperations.Case Description In two patients with giant aneurysms, the subclavian artery and femoral vein were cannulated. The first patients' operation was combined with aortic valve replacement. The pulsating mass could be removed. The second patients' operation was planned as an off-pump coronary artery bypass grafting. Upon surgical entry, the aneurysm ruptured and the operation was continued as on-pump beating-heart procedure.Conclusion Because of better follow-up and increasing use of diagnostics, more patients with graft aneurysms will be identified. The question about a treatment algorithm might be answered by aging population and improved survival.
Keywords: surgery; complications; reoperation; off-pump surgery; coronary artery bypass grafts surgery; aneurysm